Inguinodynia after inguinal hernioplasty - clinical and surgical management: a literature review - Boaventura, Fernanda Moreira; Santos, Mariana Mussalem; Perondini, Mariana Tafner; de Lima, Pedro Guimenti Ribeiro; Gentile, João Kleber de Almeida (Brazilian Journal of Case Reports, 2022)
Inguinodynia (chronic inguinal pain) is one of the most feared complications for surgeons after inguinal hernia repair with prosthetic mesh placement. The biopsychosocial impact of this complication can lead to a considerable decrease in patients quality of life. Chronic inguinal pain can appear at varying periods after surgery, for weeks to years after the surgical procedure. The pain is classified as neuropathic and non-neuropathic related to nerve injury and mesh, respectively. The diagnosis and clinical management of this condition is a separate challenge for medical specialists in hernia surgery, requiring a thorough knowledge of inguinal anatomy, advanced surgical knowledge, and literature references on the subject are still limited. In this article we discuss the diagnostic and therapeutic tools as well as the surgical maneuvers for the intervention of inguinodynia.